The Impact of Hospital Volume and Charlson Score on Postoperative Mortality of Proctectomy for Rectal Cancer: A Nationwide Study of 45, 569 Patients. Issue 5 (November 2018) - El Amrani, Mehdi; Clement, Guillaume; Lenne, Xavier; Rogosnitzky, Moshe; Theis, Didier; Pruvot, François-René; Zerbib, Philippe
Abstract : Objective: To identify the impact of hospital volume according to Charlson Comorbidity Index (ChCI) on postoperative mortality (POM) after rectal cancer surgery. Background: A volume–outcome relationship has been established in complex surgical procedures. However, little is known regarding the impact of hospital volume on POM according to patients' comorbidities after rectal cancer surgery. Methods: All patients undergoing proctectomy for cancer from 2012 to 2016 were identified in the French nationwide database. Patient condition was assessed on the basis of the validated ChCl and was stratified into 3 groups according to the score (0–2, 3, and ≥4). Chi-square automatic interaction detector (CHAID) was used to identify the cut-off values of the annual proctectomy caseload affecting the 90-day POM. The 90-day POM was analyzed according to hospital volume (low: <10, intermediate: 10–40, and high: ≥41 cases/yr) and ChCI. Results: Among 45, 569 rectal cancer resections, the 90-day POM was 3.5% and correlated to ChCI (ChCI 0–2: 1.9%, ChCI 3: 4.9%, ChCI ≥4: 5.8%; P < 0.001). There was a linear decrease in POM with increasing hospital volume (low: 5.6%, intermediate: 3.5%, high: 1.9%; P < 0.001). For low-risk patients (ChCl 0–2), 90-day POM was significantly higher in low and intermediate hospital volume compared with high hospital volume centers (3.2% and 1.8% vs 1.1%; P < 0.001). A significant decrease in postoperative hemorrhage complication rates was observed with increasing center volume (low: 13.3%, intermediate: 11.9%, and high: 9.4%; P < 0.001). After multivariable analysis, proctectomy in low [odds ratio (OR) 2.1, 95% confidence interval (CI) 1.71–2.58, P < 0.001] and intermediate (OR 1.45, 95% CI 1.2–1.75, P < 0.001) hospital volume centers were independently associated with higher risk of mortality. Conclusion: The POM after proctectomy for rectal cancer is strongly associated with hospital volume independent of patients' comorbidities. To improve postoperative outcomes, rectal surgery should be centralized. Abstract : Supplemental Digital Content is available in the text